2023
DOI: 10.5194/egusphere-egu23-13475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution and drivers of soil bacterial communities across different soil management practices and soil diagnostic units in agricultural ecosystems

Abstract: <p>Soil bacterial communities play an important role in soil health, carbon (C), and nutrient cycling, as well as in soil-plant relationships in agroecosystems. However, our understanding of the drivers and distribution of soil bacterial communities across landscapes is limited. For example, it is not clear how changes in soil management practices (i.e. Till vs No-till vs cover crop), soil diagnostic units, and their associated physical-chemical properties interact to influence the composition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, it was also revealed that REs may promote the growth of alfalfa under salt stress by regulating the bacterial community structure in the soil, such as increasing the proportion of bacteria such as Gemmatimonadota , increasing the availability of nitrogen in the soil, and improving the resistance and resilience of the ecosystem by enhancing the resistance and growth ability of plants. Research has demonstrated that alterations in the soil bacterial community’s structure can impact soil health, agricultural productivity, and ecosystems [ 84 ]. Under salt stress, the core groups of bacterial communities often shift from eutrophication to oligotrophy, resulting in alterations in nutrient utilization patterns and other environmental factors [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was also revealed that REs may promote the growth of alfalfa under salt stress by regulating the bacterial community structure in the soil, such as increasing the proportion of bacteria such as Gemmatimonadota , increasing the availability of nitrogen in the soil, and improving the resistance and resilience of the ecosystem by enhancing the resistance and growth ability of plants. Research has demonstrated that alterations in the soil bacterial community’s structure can impact soil health, agricultural productivity, and ecosystems [ 84 ]. Under salt stress, the core groups of bacterial communities often shift from eutrophication to oligotrophy, resulting in alterations in nutrient utilization patterns and other environmental factors [ 85 ].…”
Section: Discussionmentioning
confidence: 99%